The physicist's approach to the travelling salesman problem—II - Gzyl, H.; Jiménez, R.; Quiroz, A.J. (Mathematical and computer modelling, 1990)
Besides correcting an error in our previous paper on the subject, a criterion based on numerical evidence is given for the choice of the number of stripes in the stripe approximation to the travelling salesman problem. Also, we give asymptotic convergence results for the length of the stripe approximation using martingale difference methods.